Induction of Translation of the Story of "Thousand and One Nights" by Abdellatif Tasouji Based on the Pattern of Jean-Rene Ladmiral - shahram delshad; seyed mehdi masbogh; salah abdi (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2016)
Jean-Rene Ladmiral, a well-known French theorist, considers components to face translation problems which should be announced and respected by the translator. This target-oriented theorist believes that limiting translation to simple encoding is not correct and paraphrasing should accompany translation. In this case, the translator will produce meaning or new creation. The following query by the use of descriptive-analytical method tries to review the translation of Tasouji from basic story of "Thousand and One Nights" according to the applicable theory of Ladmiral that will evaluate translator's performance in the translation of source text. By accepting this principle that the most suitable method for translating the book of "Thousand and One Nights" is target-oriented and free one that pays attention to the meaning and sense rather than vocabularies and phrases, Writers of this article consider Ladmiral theory as the most congruous theory with this principle. Therefore, they have used Ladmiral nominated components as the basic standard to review and evaluate Strengths and weaknesses of Tasouji Translation. The result of the study indicates that Tasouji translation has considerable alignment with Ladmiral theory and translator could create beautiful artwork which is in accordance with the cultural context of target language while considering recreation and producing sense as well.